Correlation of the Adverse Event Following Immunization with the Severity of COVID-19 Infection in Health Care Workers in Padang - Sabrina Ermayanti; Fenty Anggrainy; Kornelis Aribowo; Muhammad Bagus H.S.; Rizki Amrika; Dwi Rizki Fadhilah (HM Publisher, 2023)
Background: Effective countermeasures to control the current COVID-19 pandemic are the implementation of health protocols and vaccinations. The problem that must be a concern after vaccination is post-immunization co-occurrence (AEFI), including COVID-19 vaccination. Another issue that is also a concern after vaccination is the incidence of being infected with COVID-19. The purpose of this study was to determine the incidence of post-vaccination COVID-19 infection in health workers in the city of Padang and its association with the incidence of COVID-19 vaccine AEFIs. Methods: The study used a descriptive-analytic design with a retrospective cohort method. The research will be carried out in all hospitals in Padang, and sampling will be carried out for 2 months, from November to December 2021. Officers who are confirmed to have COVID-19 after vaccination and meet the inclusion criteria are healthcare workers who have received at least 2 vaccines and are willing to fill out a Google form. Results: The characteristics of health workers in Padang who were confirmed to have COVID-19 after 2 vaccinations were mostly (68.1%) early adults (26-35 years), the sex was mostly female as much as 77.3%, and most professions were workers. Paramedics (nurses or midwives) as much as 57.0%. The most comorbid obesity is as much as 3.4%. Nutritional status assessed by BMI showed that obesity (37.7%) and normal nutritional status (32.9%) had almost the same proportion. Almost all health workers with or without AEFI experience mild COVID-19, as many as 98%, and experience COVID-19 infection 28 days after vaccination. Conclusion: The incidence of AEFI is not related to the severity of post-vaccination COVID-19 infection in health workers in Padang.